Linguistic Integration of the Descendants of Foreign Immigrants in Catalonia - Amado ALARCÓN ALARCÓN; Sònia PARELLA RUBIO (El Colegio de la Frontera Norte, A.C., 2013)
This article analyzes the linguistic integration of the second generation of immigrants in Catalonia on the basis of the theory of segmented assimilation. The main objectives are to discover which factors help to determine the preference for the Catalan language (to the detriment of Spanish and the languages of origin) and the acquisition of written skills in Catalan among these young people. The sample comprises 3 578 descendants of foreign immigrants aged between 12 and 17. Various multivariable logistic regression models have been carried out on the basis of theoretically relevant predictors. The results of the analysis show that there are different itineraries for linguistic adaptation among the teenage children of immigrants, reflecting a linguistic segmentation. The text examines the theoretical and political implications of the results in the Catalan context.